Hubungan Pengetahuan dan Sikap Ibu dengan Pemberian MPASI Dini di Wilayah Kerja Klinik Pratama Gita Deli Tua Desa Kedai Durian Tahun 2023 - Sartika Sartika; Dessy Ratna Sari; Ninsah Mandala Putri Sembiring; Lasria Simamora; Indra Septian Manurung (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Early complementary food is food or drink given to babies aged 6 months. The research objective was to determine the relationship between knowledge and attitudes of mothers and the provision of complementary feeding at PMB Irma Suryani, Prabumulih City in 2023. The research method is analytic in nature, using a cross sectional approach. The population of this study were all mothers who had babies aged ≥ 6 – 24 months at PMB Irma Suryani Prabumulih City in 2023. Sampling in this study used the Accidental Sampling method, namely 45 respondents. The research instrument is a questionnaire. From the bivariate analysis it was found that of the 33 respondents who had good knowledge, there were 30 respondents (66.7%) who gave complementary foods and from 12 respondents who had less knowledge, there were 5 respondents (11.1%) who gave complementary foods. From 37 respondents who had a good attitude, there were 33 respondents (73.3%) who gave complementary foods and of the 8 respondents who had a poor attitude, there were 2 respondents (4.4%) who gave complementary foods. It can be concluded that there is a significant relationship between knowledge and the provision of complementary foods with a P value 0.000 < α 0.05, there is a significant relationship between the mother's attitude and the provision of complementary foods with a P value 0.000 < α 0.05.